WHICH IS MORE EFFECTIVE, A MIND MAP OR A CONCEPT MAP LEARNING STRATEGY? - I Wayan Redhana; Kadek Widiastari; Achmad Samsudin; Irwanto Irwanto (Jurnal Cakrawala Pendidikan, 2021)
A mind map and a concept map learning strategy are two learning strategies that are often used to improve students’ learning achievement. This study aimed to describe the differences in learning achievement between students who studied with a mind map learning strategy and those who used the concept map learning strategy, as well as the students’ responses toward the learning strategy applied. This type of study was a quasi-experiment with a pretest-posttest control group design. The methods used in this study were a test and a questionnaire. Data of students’ learning achievement were analyzed using inferential statistics of covariance analysis, while data of students’ responses were analyzed by descriptive statistics. The results of the study indicated that there were significant differences in the learning achievement between students who used the mind map learning strategy and those who studied with the concept map learning strategy. Those who used the mind map learning strategy had better achievements than those using the concept map learning strategy. In addition, the students’ responses were more positive toward the mind map learning strategy than to the concept map learning strategy.